Worlding hydropower: river realities in the Chilean Patagonia. Issue 1 (1st January 2019) - Hernando-Arrese, Maite; Tironi, Manuel
ABSTRACT: Based on the case of HidroAysén, in this paper we discuss the different modes of existence of a hydroelectric project. Inspired by an ontological sensibility and the idea of worlding, we sustain that hydroelectric energy is embedded in, and is the source of, multiple worlds where different ontologies of water and energy meet, not always peacefully. Drawing on in-depth interviews and documentary sources, we identify three worlds or realities – yet not entirely autonomous – in which the HidroAysén project exists: the National Hydropower World, the Market Hydropower World, and the Sustainable Hydropower World. We argue that these three realities, through different ecologies, knowledge, and narratives, execute different parameters of reality and objectivity. Our final argument is that an ontological approach to analyze hydropower development and the conflicts that it has spurred can stimulate new ways of thinking about taken-for-granted assumptions, categories, and practices regarding the way hydropower is or might be produced.